Proceedings of the 52 Annual Conference of The Israel Society for the Promotion of Classical Studies. (Scripta Classica Israelica, 2025)
The article presents the program schedule for a conference on classical studies, including sessions on Socrates, the Roman Empire, and Jewish writing including Socrates and emotions, Roman Empire society, and Jewish history in antiquity.